Force-velocity profiles in CrossFit athletes: A cross-sectional study considering sex, age, and training frequency - Juan A. PARRAGA-MONTILLA; Jose C. CABRERA LINARES; Pedro JIMENEZ REYES; Manuel MOYANO LOPEZ; Victor SERRANO HUETE; Jose A. MORCILLO LOSA; Pedro A. LATORRE ROMAN (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: The force-velocity profile has been analysed previously in different sports modalities; nevertheless, it has not been analysed in CrossFit. Objective: The aim of this study was to report neuromuscular characteristics of CrossFit athletes using their individual force-velocity profile, investigating differences according to sex, age, and training frequency. Materials and Methods: 72 males (33.17 ± 6.86 years; BMI: 25.93 ± 3.64 kg/m2) and 18 females (30.11 ± 6.92 years; BMI: 23.53 ± 3.98 kg/m2) participated in this study. The force-velocity profile was calculated using Samozino's method. Furthermore, neuromuscular characterization was completed with a squat jump and three drop jumps (20, 30, and 40 cm). Results: Regarding sex, significant differences in all analysed mechanical variables (p < 0.001) were found except for the theoretical maximal force (p = 0.944). No significant differences were found between age groups. Considering training frequency, athletes who train more than 5 days per week showed higher performance in all analysed mechanical variables (p < 0.05). Conclusion: CrossFit athletes have a force-velocity profile more oriented towards velocity than force. Males and females have different neuromuscular characteristics, also neuromuscular improvements can be achieved at any age. Moreover, higher neuromuscular performance is developed with a training frequency of 5 days or more per week.